Mineralogy of phosphate accumulations in the Huber stock, Krasno ore district, Slavkovsky les area, Czech Republic - Sejkora,J.; Skoda,R.; Ondrus,P.; Beran,P.; Susser,C. (Journal of the Czech Geological Society, 2006)
The present detailed research is focused on minerals of phosphate accumulations collected in the Huber open pit and at the 5th level of the Huber shaft, Krasno ore district, Slavkovsky les area, Czech Republic. The following minerals have been identified at the studied localities: benyacarite, beraunite, cacoxenite, chalcosiderite, crandallite, dufrenite, earlshannonite, fluellite, fluorapatite, frondelite, goyazite, isokite, kolbeckite, leucophosphite, morinite, natrodufrenite, phosphosiderite, rockbridgeite, strengite, triplite, turquoise, vivianite, wavellite, waylandite, whitmoreite and zwieselite. A brief review of evolution of the phosphate mineral associations at the two studied localities is presented.
Keywords: Huber stock; Krasno near Horni Slavkov; Slavkovsky les area; greisen; phosphate minerals; mineralogy; X-ray powder diffraction data; chemical data